General Provisions and Judicial Organization According to Code of Civil Procedure of Serbia from 1865 - Kulauzov, Maša; Milutin, Milan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In the paper authors give legal history analysis of provisions of legislation on civil procedure regarding general rules and judicial organization. Minister of Justice Rajko Lešjanin prepared the draft and consigned it to State Council for approval. Part of draft concerning common provisions and organization of courts was not accepted in its original version, only after certain changes and supplements. Valuable source for aforementioned amendments is archival material stored in the fond of the State Council, in the State Archive of Serbia. In the article special attention was given to unenacted draft consisting of changes and supplements of some code provisions, prepared by then minister of justice Stojan Veljković in 1872. Although above-mentioned draft never came into force, constructive discussion that had developed between the author of the draft, State Councilʼs Commission and district courts served as a base for partial revision of certain provisions of Code of Civil Procedure, among which the most important one is introduction of two-stage decision making in municipal courts (par. 15). Original text of the draft has not been preserved, but in the fond of the Ministry of Justice in The State Archive of Serbia one can find opinions of State Councilʼs Commission and district courts that were used as a key historical source for writing the article.